Two rhombognathine mites (Acari: Halacaridae) from the Gulf of Oman, Iran - Hiroshi Abé; Isa Etemadi (Persian Journal of Acarology)
This paper presents information on the Iranian halacarid fauna providing the first record of the genus Rhombognathus from the Gulf of Oman. Two species of the genus Rhombognathus are described from the Iranian coast, viz. Rhombognathus scutulatus Bartsch 1983 and R. iranius sp. nov.